Gel polymer electrolyte and electrochemical device containing said gel polymer electrolyte
The gel polymer electrolyte, with its specific matrix polymer structure and non-aqueous solvent composition, addresses the challenges of high voltage stability and battery resistance in lithium secondary batteries, resulting in improved performance and safety.
Patent Information
- Application Number
- JP2024560754
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-14
- Filing Date
- 2023-04-14
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2043-04-14
AI Technical Summary
Existing gel polymer electrolytes for lithium secondary batteries face challenges in achieving high voltage stability and reducing battery resistance while maintaining mechanical strength and safety.
A gel polymer electrolyte is developed, comprising a matrix polymer formed by polymerizing an oligomer with a specific chemical formula, which creates a three-dimensional network structure. This electrolyte includes a lithium salt and a non-aqueous solvent, such as cyclic carbonate or alkyl ether compounds, to enhance lithium ion conductivity and stability.
The proposed gel polymer electrolyte improves high voltage stability, reduces battery resistance, and maintains mechanical strength, leading to enhanced performance and safety of lithium secondary batteries.
Smart Images

Figure 2025513895000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims priority to Korean Patent Application No. 10-2022-0046564, filed on April 14, 2022. The present invention relates to a gel polymer electrolyte and a lithium secondary battery including the gel polymer electrolyte. [Background technology]
[0002] As technological development and demand for mobile devices increases, the demand for secondary batteries as an energy source is growing rapidly. Among secondary batteries, lithium secondary batteries, which have high energy density and voltage, have been commercialized and are widely used.
[0003] A lithium secondary battery is manufactured by applying a positive electrode active material and a negative electrode active material to a current collector in an appropriate thickness or forming the active material itself into a film of an appropriate length, and then winding or laminating the electrode assembly together with a separator, which is an insulator, to manufacture an electrode assembly, placing the electrode assembly in a can or a similar container, and then injecting an electrolyte.
[0004] The positive electrode active material is a lithium metal oxide, and the negative electrode active material is a lithium metal, a lithium alloy, crystalline carbon, amorphous carbon, or a carbon composite. The electrolyte is primarily a liquid electrolyte, particularly an ion-conductive liquid electrolyte in which a salt is dissolved in a non-aqueous organic solvent.
[0005] However, as interest in energy storage technology increases, there is a demand for the development of secondary batteries that are small and lightweight, capable of high-capacity charging and discharging, and have safety at high temperatures and high voltages. Therefore, in recent years, the development of batteries using gel polymer electrolytes made of gel polymers rather than liquid electrolytes has been attracting attention.
[0006] It is generally known that the safety of a battery improves in the following order: liquid electrolyte < gel polymer electrolyte < solid polymer electrolyte, while the performance of the battery decreases in the latter case.
[0007] That is, the gel polymer electrolyte has a disadvantage that the conductivity of lithium ions is lower than that of a liquid electrolyte consisting of only an electrolytic solution. To improve this, a method of reducing the thickness of the gel polymer electrolyte has been proposed. However, in this case, the mechanical strength is reduced, and problems occur in the performance and safety of the battery, such as short circuits between the positive and negative electrodes and the gel polymer electrolyte during the manufacture of the battery.
[0008] Therefore, there is a need for the development of a gel polymer electrolyte that improves both the safety and performance of batteries. Summary of the Invention [Problem to be solved by the invention]
[0009] An object of the present invention is to provide a gel polymer electrolyte capable of realizing the effects of increasing high voltage stability and reducing battery resistance.
[0010] Another object of the present invention is to provide the above-mentioned gel polymer electrolyte composition.
[0011] It is still another object of the present invention to provide a lithium secondary battery containing the gel polymer electrolyte.
[0012] It will be readily apparent to those skilled in the art that other objects and advantages of the present invention can be realized by the means recited in the claims and combinations thereof. [Means for solving the problem]
[0013] A first aspect of the present invention relates to a gel polymer electrolyte, the gel polymer electrolyte comprising a matrix polymer and an electrolyte solution impregnated in the matrix polymer, the matrix polymer being formed into a three-dimensional network structure by polymerization of an oligomer represented by the following Chemical Formula 1, the electrolyte solution comprising a lithium salt and a non-aqueous solvent, the non-aqueous solvent comprising at least one selected from the group consisting of a cyclic carbonate-based compound, a linear carbonate-based compound, an alkyl ether-based compound, an alkyl acetate-based compound, an alkyl propionate-based compound, and a nitrile-based compound.
[0014] [ka]
[0015] In Chemical Formula 1, r is an integer equal to or greater than 1; R1 is an aliphatic hydrocarbon group or an aromatic hydrocarbon group, R2 and R5 each independently represent an alkyl group having 1 to 3 carbon atoms in which at least one hydrogen has been substituted with a fluorine; R3 is an alkyl group having n carbon atoms in which all hydrogen atoms are substituted with fluorine atoms, R4 is an alkyl group having n-1 carbon atoms in which all hydrogen atoms are substituted with fluorine atoms, and n is 2 or 3; Either one of p and q may be 0 or both may be integers of 1 or more. When both p and q are integers of 1 or more, p / q has a value of 1 / 9 to 9 / 1; R6 and R7 each independently represent a linear or branched alkyl group having 1 to 5 carbon atoms; The R8 is null or a methyl group, and the m is any one of integers 1, 2, 3, 4, and 5.
[0016] According to the second aspect of the present invention, in the first aspect, the oligomer includes a unit A represented by the following chemical formula 2, a unit B represented by the following chemical formula 3, and a unit C represented by the following chemical formula 4:
[0017] [ka]
[0018] [ka]
[0019] [ka]
[0020] In Chemical Formula 2, Chemical Formula 3, and Chemical Formula 4, r is an integer equal to or greater than 1; R1 is an aliphatic hydrocarbon group or an aromatic hydrocarbon group, R2 and R5 each independently represent an alkyl group having 1 to 3 carbon atoms in which at least one hydrogen has been substituted with a fluorine; R3 is an alkyl group having n carbon atoms in which all hydrogen atoms are substituted with fluorine atoms, R4 is an alkyl group having n-1 carbon atoms in which all hydrogen atoms are substituted with fluorine atoms, and n is 2 or 3; Either one of p and q may be 0 or both may be integers of 1 or more. When both p and q are integers of 1 or more, p / q has a value of 1 / 9 to 9 / 1; R6 and R7 each independently represent a linear or branched alkyl group having 1 to 5 carbon atoms; The R8 is null or a methyl group, and the m is any one of integers 1, 2, 3, 4, and 5.
[0021] According to a third aspect of the present invention, in the second aspect, the formula 2 can be divided into a unit represented by the following formula 2-1 and a unit represented by the following formula 2-2.
[0022] [ka]
[0023] [ka]
[0024] In Chemical Formula 2-2, R1 is an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, or an aromatic hydrocarbon group.
[0025] According to a fourth aspect of the present invention, in the third aspect, the aliphatic hydrocarbon group is an alkylene group having 1 to 20 carbon atoms; an alkylene group having 1 to 20 carbon atoms containing an isocyanate group (NCO); an alkoxylylene group having 1 to 20 carbon atoms; an alkenylene group having 2 to 20 carbon atoms; or an alkynylene group having 2 to 20 carbon atoms, the alicyclic hydrocarbon group is a substituted or unsubstituted cycloalkylene group having 4 to 20 carbon atoms; a substituted or unsubstituted cycloalkylene group containing an isocyanate group (NCO) and having 4 to 20 carbon atoms; a cycloalkenylene group having 4 to 20 carbon atoms; or a heterocycloalkylene group having 2 to 20 carbon atoms; The aromatic hydrocarbon group is a substituted or unsubstituted arylene group having 6 to 20 carbon atoms; or a heteroarylene group having 2 to 20 carbon atoms.
[0026] According to the fifth aspect of the present invention, in the fourth aspect, the structure represented by the chemical formula 2-2 is derived from any one of the compounds represented by the following chemical formulae a to n.
[0027] [ka]
[0028] [ka]
[0029] [ka]
[0030] [ka]
[0031]
change
[0032]
change
[0033]
change
[0034]
change
[0035]
change
[0036]
change
[0037]
change
[0038]
change
[0039]
change
[0040]
change
[0041] According to a sixth aspect of the present invention, in the fourth aspect, the structure represented by the chemical formula 2-2 is any one of structures represented by the following chemical formulae o to x.
[0042] [ka]
[0043] [ka]
[0044] [ka]
[0045] [ka]
[0046] [ka]
[0047] [ka]
[0048] [ka]
[0049] [ka]
[0050] [ka]
[0051] [ka]
[0052] According to a seventh aspect of the present invention, in any one of the second to sixth aspects, the Chemical Formula 4 provides (meth)acryloyl groups to both ends of the oligomer of the Chemical Formula 1.
[0053] According to an eighth aspect of the present invention, in any one of the first to seventh aspects, the oligomer includes a compound represented by the following chemical formula 5.
[0054] [ka]
[0055] According to a ninth aspect of the present invention, in any one of the first to eighth aspects, the oligomer has a weight average molecular weight (Mw) of about 1,000 g / mol to 500,000 g / mol.
[0056] According to a tenth aspect of the present invention, in any one of the first to ninth aspects, the matrix polymer further contains 5 to 700 parts by weight of inorganic particles based on 100 parts by weight of the oligomer.
[0057] According to an eleventh aspect of the present invention, in any one of the first to tenth aspects, the gel polymer electrolyte has a gel content of about 1 wt % or more at a temperature of 25°C.
[0058] A twelfth aspect of the present invention relates to a lithium ion secondary battery, the secondary battery including a negative electrode, a positive electrode, and a gel polymer electrolyte, the gel polymer electrolyte being according to any one of the first to eleventh aspects.
[0059] A thirteenth aspect of the present invention relates to a composition for a gel polymer electrolyte, the composition comprising a lithium salt, a non-aqueous solvent, a polymerization initiator, and an oligomer represented by the following chemical formula 1, the oligomer being included in an amount of 0.5% by weight to 20% by weight based on the total weight of the composition for a gel polymer electrolyte:
[0060] [ka]
[0061] In Chemical Formula 1, r is an integer equal to or greater than 1; R1 is an aliphatic hydrocarbon group or an aromatic hydrocarbon group, R2 and R5 each independently represent an alkyl group having 1 to 3 carbon atoms in which at least one hydrogen has been substituted with a fluorine; R3 is an alkyl group having n carbon atoms in which all hydrogen atoms are substituted with fluorine atoms, R4 is an alkyl group having n-1 carbon atoms in which all hydrogen atoms are substituted with fluorine atoms, and n is 2 or 3; Either one of p and q may be 0 or both may be integers of 1 or more. When both p and q are integers of 1 or more, p / q has a value of 1 / 9 to 9 / 1; R6 and R7 each independently represent a linear or branched alkyl group having 1 to 5 carbon atoms; The R8 is null or a methyl group, and the m is any one of integers 1, 2, 3, 4, and 5. Effect of the Invention
[0062] The gel polymer electrolyte according to one embodiment of the present invention includes a matrix polymer made of an oligomer including a fluorine-substituted polyether unit and at least one acrylate unit at its terminal, which increases the degree of freedom of Li ions through immobilization and stabilization of anions, thereby reducing battery resistance and achieving high lithium ion conductivity. In addition, the matrix polymer structure in the gel polymer electrolyte increases high-temperature durability, allowing the manufacture of a lithium secondary battery with improved stability at high voltages and high temperatures.
[0063] The drawings attached to this specification are intended to illustrate preferred embodiments of the present invention and serve to further understand the technical ideas of the present invention as well as the contents of the invention, and therefore the present invention should not be interpreted as being limited to only the matters described in the drawings. Meanwhile, the shape, size, scale, or ratio of elements in the drawings attached to this specification may be exaggerated in order to emphasize a clearer description. [Brief description of the drawings]
[0064] [Figure 1] 1 is a graph showing comparative experimental results of heat generation safety of batteries according to Example 1 and Comparative Example 1. [Diagram 2] 1 is a graph showing a comparison of experimental results of capacity retention rate and resistance increase rate of batteries according to Example 1 and Comparative Example 1. [Diagram 3] 1 shows the results of a hot box test of the battery according to Example 2. [Figure 4] 1 shows the results of a hot box test of the battery according to Comparative Example 2. [Diagram 5] FIG. 13 is a graph showing the capacity and thickness change rate when the batteries according to Example 2 and Comparative Example 2 are repeatedly charged and discharged. [Figure 6] 1 is a photographic image of the battery of Example 2 subjected to hot box testing. [Figure 7] 1 is a photographic image of a battery of Comparative Example 2 that was subjected to a hot box test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0065] The present invention will be described in detail below. Prior to this, the terms and words used in the present specification and claims are not to be interpreted as being limited to their ordinary and dictionary meanings, but are to be interpreted as being in accordance with the meaning and concept of the technical idea of the present invention, in accordance with the principle that the inventor himself can appropriately define the concept of the term in order to best describe the invention. Therefore, it should be understood that the embodiment described in this specification and the configuration shown in the drawings are merely the most preferred embodiment of the present invention, and do not represent the entire technical idea of the present invention, and therefore there may be various equivalents and modifications that can be substituted therefor at the time of this application.
[0066] Throughout the specification, when a part "comprises" another component, it does not mean excluding the other component, but may further include the other component, unless otherwise specified.
[0067] In addition, the terms "about," "substantially," and the like, used throughout this specification, when given manufacturing and material tolerances inherent in the recited meaning, are used to mean a numerical value or close to the numerical value, in order to prevent unconscionable infringers from unfairly using disclosure content in which precise or absolute numerical values are recited to aid in the understanding of this application.
[0068] Throughout this specification, the phrase "A and / or B" means "A, B, or all of these."
[0069] Meanwhile, in this specification, the term "repeating unit" refers to a unit formed by polymerizing a monomer and derived from the monomer. The repeating unit may be a unit formed directly by a polymerization reaction, or may be a unit in which a part of the unit is converted into a different structure by treating the polymer.
[0070] In the present invention, unless otherwise specified, "*" means the same or different atoms, or a portion where the ends of a chemical formula are linked together.
[0071] In general, gel-type polymer electrolytes are inferior to solid polymer electrolytes in terms of high voltage safety and mechanical properties, and have disadvantages such as lower battery resistance and ionic conductivity compared to liquid electrolytes.
[0072] In recent years, therefore, research has been conducted to improve lithium ion conductivity while ensuring high voltage stability by using copolymers such as oligomers. However, when using oligomer compounds, it is difficult to control physical properties and also difficult to form a uniform polymer in the battery, making it difficult to apply them to high-capacity and large-sized batteries.
[0073] Therefore, the present invention aims to solve such problems by providing a gel polymer electrolyte containing a matrix polymer formed from an oligomer compound produced by polymerizing compounds having physical properties that can mutually complement each other in terms of electrochemical properties and mechanical properties.
[0074] Specifically, one embodiment of the present invention comprises a matrix polymer; an electrolyte impregnated in the matrix polymer; The matrix polymer is formed into a three-dimensional network structure by polymerization of an oligomer represented by the following chemical formula 1: The oligomer provides a gel polymer electrolyte including a unit A represented by the following Chemical Formula 2, a unit B represented by the following Chemical Formula 3, and a unit C represented by the following Chemical Formula 4:
[0075] [ka]
[0076] In Chemical Formula 1, r is an integer equal to or greater than 1; R1 is an aliphatic hydrocarbon group or an aromatic hydrocarbon group, R2 and R5 each independently represent an alkyl group having 1 to 3 carbon atoms in which at least one hydrogen has been substituted with a fluorine; R3 is an alkyl group having n carbon atoms in which all hydrogen atoms are substituted with fluorine atoms, R4 is an alkyl group having n-1 carbon atoms in which all hydrogen atoms are substituted with fluorine atoms, and n is 2 or 3; Either one of p and q may be 0 or both may be integers of 1 or more. When both p and q are integers of 1 or more, p / q may have a value of 1 / 9 to 9 / 1; R6 and R7 may each independently be a linear or branched alkyl group having 1 to 5 carbon atoms. In a more specific embodiment, R6 may be a linear or branched alkyl group having 2 to 4 carbon atoms.
[0077] In addition, R8 is null or a methyl group, and m is any one of integers 1, 2, 3, 4, and 5.
[0078] In the present invention, the explanations about R1 to R7, r, p, and q also apply to the following Chemical Formula 2, Chemical Formula 3, Chemical Formula 4, and Chemical Formula 5.
[0079] Hereinafter, Chemical Formula 1 will be described in detail by dividing it into the unit A (Chemical Formula 2), the unit B (Chemical Formula 3), and the unit C (Chemical Formula 4) which constitute Chemical Formula 1.
[0080] [ka]
[0081] In the above formula 2, p, q and r are the numbers of repeating units. The unit A can be divided into a unit A-1 represented by chemical formula 2-1 and a unit A-2 represented by chemical formula 2-2 as shown below, which will be described below separately for chemical formula 2-1 and chemical formula 2-2. In the chemical formula 2, r is an integer of 1 or more and can have a value of 1 to 20. The molecular weight (Mw) of the unit A represented by chemical formula 2 can have a value of 100 to 100,000.
[0082] [ka]
[0083] In the above formula 2-1, R2 and R5 are each independently an alkyl group having 1 to 3 carbon atoms in which at least one hydrogen is substituted with a fluorine. R3 is an alkyl group having n carbon atoms in which all hydrogens are substituted with fluorine, and R4 is an alkyl group having n-1 carbon atoms in which all hydrogens are substituted with fluorine, where n is 2 or 3. In the above formula 2-1, either one of p and q may be 0 or both may be integers of 1 or more. If both p and q are integers of 1 or more, p / q may have a value of 1 / 9 to 9 / 1.
[0084] [ka]
[0085] In formula 2-2, R1 can be an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, or an aromatic hydrocarbon group.
[0086] In one embodiment of the present invention, the aliphatic hydrocarbon group is an alkylene group having 1 to 20 carbon atoms; an alkylene group having 1 to 20 carbon atoms containing an isocyanate group (NCO); an alkoxylene group having 1 to 20 carbon atoms; an alkenylene group having 2 to 20 carbon atoms; or an alkynylene group having 2 to 20 carbon atoms, the alicyclic hydrocarbon group is a substituted or unsubstituted cycloalkylene group having 4 to 20 carbon atoms; a substituted or unsubstituted cycloalkylene group containing an isocyanate group (NCO) and having 4 to 20 carbon atoms; a cycloalkenylene group having 4 to 20 carbon atoms; or a heterocycloalkylene group having 2 to 20 carbon atoms; The aromatic hydrocarbon group may be a substituted or unsubstituted arylene group having 6 to 20 carbon atoms; or a heteroarylene group having 2 to 20 carbon atoms.
[0087] In one embodiment of the present invention, the structure represented by Chemical Formula 2-2 may be derived from any one of the compounds represented by Chemical Formulae a to n below.
[0088]
change
[0089]
change
[0090]
change
[0091]
change
[0092]
change
[0093]
change
[0094]
change
[0095]
change
[0096]
change
[0097]
change
[0098]
change
[0099] [ka]
[0100] [ka]
[0101] [ka]
[0102] The unit A contains a fluorine-substituted ether in its structure, and thus can achieve the effects of improving high voltage safety, reducing battery resistance, and improving ionic conductivity through the effects of stabilizing anions and increasing oxidation safety.
[0103] Meanwhile, in a specific embodiment of the present invention, the structure of the formula 2-2 may be any one of the following formulae o to x.
[0104] [ka]
[0105] [ka]
[0106] [ka]
[0107] [ka]
[0108] [ka]
[0109] [ka]
[0110] [ka]
[0111] [ka]
[0112] [ka]
[0113] [ka]
[0114] In one embodiment of the present invention, the unit B may be represented by the following Formula 3:
[0115] [ka]
[0116] In the formula 3, the * on both sides are the moieties connected to the unit A-1 and the unit C described below. For details about R1 in the formula 3, see the description of R1 in the formula 2-2 above.
[0117] Meanwhile, in a specific embodiment of the present invention, the structure represented by Chemical Formula 3 may be the structures represented by Chemical Formulae o to x as described above. In one embodiment of the present invention, the unit C may be represented by Formula 4 below.
[0118] [ka]
[0119] The unit C is bonded to both ends of the oligomer and provides functional groups capable of reacting with a crosslinking agent at both ends of the oligomer. In the formula 4, R6 and R7 may each independently be a linear or branched alkyl group having 1 to 5 carbon atoms. In a more specific embodiment, R6 may be a linear or branched alkyl group having 2 to 4 carbon atoms. R8 may be null or a methyl group. In addition, m is an integer of 1, 2, 3, 4, or 5. That is, the unit C can provide (meth)acryloyl groups at both ends of the oligomer.
[0120] In the gel polymer electrolyte of the present invention, the oligomer may include, as a representative example, a compound represented by the following Chemical Formula 5.
[0121] [ka]
[0122] The present invention will be described in more detail below with reference to examples. However, the following examples are merely for the purpose of illustrating the present invention, and the scope of the present invention is not limited thereto.
[0123] The weight average molecular weight (Mw) of the oligomer for forming the gel polymer electrolyte of the present invention may be about 1,000 g / mol to 500,000 g / mol, specifically 1,000 g / mol to 100,000 g / mol. When the weight average molecular weight of the oligomer is within the above range, the mechanical strength of the battery containing it can be effectively improved.
[0124] When the weight average molecular weight of the copolymer is within the above range, it is possible to ensure mechanical properties, processability (moldability), electrochemical stability, etc. In this case, in the unit A represented by Chemical Formula 1, p, q, and r may be appropriately changed within the above range according to the weight average molecular weight of the copolymer.
[0125] In this case, the weight average molecular weight can be measured using gel permeation chromatography (GPC). For example, after preparing a sample of a certain concentration, the GPC measurement system alliance 4 instrument is stabilized. Once the instrument is stabilized, a standard sample and a sample are injected into the instrument to obtain a chromatogram, and then the molecular weight is calculated according to the analysis method (system: Alliance 4, column: Ultrahydrogel linear x 2, eluent: 0.1 M NaNO3 (pH 7.0 phosphate buffer, flow rate: 0.1 mL / min, temperature: 40°C, injection: 100 μL).
[0126] Meanwhile, when the gel polymer electrolyte of the present invention is embodied as a coating type gel polymer electrolyte, the matrix polymer may further include 5 to 700 parts by weight, specifically 100 to 400 parts by weight, of inorganic particles based on 100 parts by weight of the oligomer.
[0127] The inorganic particles are preferably included in an amount of 700 parts by weight or less in order to effectively prevent an increase in the interfacial resistance with the electrode. If the inorganic particles are included in an amount exceeding 700 parts by weight, pores may be formed in the electrolyte, resulting in a decrease in ion conductivity. Also, if the content of the inorganic particles is less than 5 parts by weight, the effect of improving electrochemical stability while ensuring mechanical properties is low.
[0128] The inorganic particles are impregnated into the matrix polymer so that the high-viscosity solvent can penetrate well through the pores formed by the spaces between the inorganic particles. In other words, by including the inorganic particles, it is possible to obtain an effect of further improving wettability with respect to the high-viscosity solvent by the affinity between polar substances and the capillary phenomenon.
[0129] Such inorganic particles have a high dielectric constant and are within the operating voltage range of a lithium secondary battery (e.g., Li / Li +Inorganic particles in which oxidation and / or reduction reactions do not occur at a reference of 0 to 5 V can be used. Specifically, representative examples of the inorganic particles include BaTiO3, BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3 (PLZT, 0 < x < 1, 0 < y < 1), Pb(Mg 1 / 3 Nb 2 / 3 )O3 - PbTiO3 (PMN - PT), hafnia (HfO2), SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiC, lithium phosphate (Li3PO4), lithium titanium phosphate (Li x1 Ti y1 (PO4)3, 0 < x1 < 2, 0 < y1 < 3), lithium aluminum titanium phosphate (Li x2 Al y2 Ti z2 (PO4)3, 0 < x2 < 2, 0 < y2 < 1, 0 < z2 < 3), 14Li2O - 9Al2O3 - 38TiO2 - 39P2O5 such as (LiAlTiP) x3 O y3 -based glass (0 < x3 < 4, 0 < y3 < 13), lithium lanthanum titanate (Li x4 La y4 TiO3, 0 < x4 < y4 < 3), Li 3.25 Ge 0.25 P 0.75 S4 such as lithium germanium thiophosphate (Li x5 Ge y5 P z S w , 0 < x5 < 4, 0 < y5 < 1, 0 < z < 1, 0 < w < 5), lithium nitride such as Li3N (Li x6 N y6 , 0 < x6 < 4, 0 < y6 < 2), SiS2 - based glass such as Li3PO4 - Li2S - SiS2 (Li x7 Si y7 S z2 , 0 < x7 < 3, 0 < y7 < 2, 0 < z2 < 4), P2S5 - based glass such as LiI - Li2S - P2S5 (Li x8 P y8 Sz3 , 0 < x8 < 3, 0 < z3 < 7), and a single substance or a mixture of two or more selected from the group consisting of lithium lanthanum zirconium oxide (Li7La3Zr2O 12 , LLZO).
[0130] The average particle size of the inorganic particles is preferably about 0.001 to 10 μm so as to be present in a uniform thickness in the gel polymer electrolyte and have an appropriate porosity. When the average particle size of the inorganic particles is less than 0.001 μm, the dispersibility decreases. When it exceeds 10 μm, not only does the thickness of the porous coating layer increase, but a phenomenon of aggregation of the inorganic particles occurs, and there is a risk that the mechanical strength decreases while being exposed outside the gel polymer electrolyte. The gel polymer electrolyte of the present invention as described above, when measured with an impedance measurement analysis system at a temperature of 25 °C, has a Li -4 ionic conductivity of 2.5×10 + S / cm or more. At this time, the ionic conductivity was measured through an alternating current impedance measurement method after sandwiching the produced gel polymer electrolyte between a pair of platinum electrode disks with a diameter of 1 cm. The measuring device used was the VMP3 model manufactured by Bio Logic, and the measurement was carried out at room temperature under the conditions of 10,000 - 0.1 Hz and an amplitude of 10 mV.
[0131] In addition, the gel polymer electrolyte may have a Li + ion migration coefficient of 0.3 or more based on the NMR measurement method at a temperature of 25 °C. At this time, the Li + ion migration coefficient can be defined as "Li + ion diffusivity / (Li + ion diffusivity + anion diffusivity)". At this time, the Li + ion diffusivity and anion diffusivity can be measured through the following devices and methods. For example, using a Varian 500 MHz NMR / dual probe, the Li + ion (cation) diffusion constant is 7 measured by Li diffusion NMR, and the anion diffusion constant is 19The measurements were performed using F diffusion NMR. The solvent used was acetone-d6, and in order to measure the diffusion value within the sample itself, an inner tube (acetone-d6) was used to prevent the sample from mixing with the deuterium solvent. In addition, a stimulated echo with gradient pulse pulse sequence was used in the measurement experiment. The gradient amplitude was adjusted so that the peak intensity at the highest gradient power was about 2-5% of the peak intensity at the lowest gradient power, and this range was divided into 16 steps, as in solution NMR, and 16 different amplitudes were applied to each sample.
[0132] In addition, the gel polymer electrolyte may have a gel content of about 1 wt % or more, specifically about 20 wt % or more, at a temperature of 25° C. The gel content may refer to the weight of other components in the gel polymer electrolyte excluding the electrolyte.
[0133] In addition, the gel polymer electrolyte preferably has an unreacted oligomer content of 20 wt % or less based on the total amount of reactive oligomers added at a temperature of 25°C.
[0134] Here, the content of the unreacted oligomer can be determined by preparing a gel polymer electrolyte, extracting the gel polymer electrolyte with a solvent (acetone), and measuring the extracted solvent by NMR.
[0135] Meanwhile, in the gel polymer electrolyte of the present invention, the electrolyte impregnated in the matrix polymer contains a conventional lithium salt-containing non-aqueous solvent, and in this case, the lithium salt may include any one selected from the group consisting of LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiN(C2F5SO2)2, LiN(CF3SO2)2, CF3SO3Li, LiC(CF3SO2)3, LiC4BO8, LiTFSI, LiFSI, and LiClO4, or a mixture of two or more of these, but is not limited thereto.
[0136] The lithium salt may be contained in the electrolyte at a molar concentration (M) to 2M, or at 10% by weight to 50% by weight based on the total content of the oligomer. In addition, the electrolyte solvent of the present invention may be a non-aqueous solvent commonly used in electrolytes for lithium secondary batteries, and representative examples thereof may include at least one compound selected from the group consisting of cyclic carbonate compounds, linear carbonate compounds, alkyl ether compounds, alkyl acetate compounds, alkyl propionate compounds, and nitrile compounds. In this case, examples of the cyclic carbonate compounds may include at least one compound selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), and fluoroethylene carbonate (FEC).
[0137] The alkyl ether compound may include at least one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, and ethyl propyl ether.
[0138] The alkyl acetate compound may include at least one selected from the group consisting of methyl acetate, ethyl acetate, and propyl acetate.
[0139] The alkyl propionate compound may include at least one selected from the group consisting of methyl propionate, ethyl propionate, propyl propionate, and butyl propionate.
[0140] The nitrile-based compound may include at least one selected from the group consisting of acetonitrile, propionitrile, butyronitrile, valeronitrile, caprylonitrile, heptanenitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, and 4-fluorophenylacetonitrile.
[0141] In particular, propylene carbonate and ethylene carbonate, which are cyclic carbonates among the carbonate-based electrolyte solvents, are highly viscous organic solvents with high dielectric constants, and can be preferably used since they can easily dissociate lithium salts in the electrolyte. If such cyclic carbonates are mixed with linear carbonates having low viscosity and low dielectric constants, such as ethyl methyl carbonate, diethyl carbonate, or dimethyl carbonate, in an appropriate ratio, an electrolyte having high electrical conductivity can be produced, and the mixture can be more preferably used.
[0142] In addition, the electrolyte solvent may contain common additives used in electrolytes to improve performance, such as vinylene carbonate (VC), 1,3-propane sultone (PS), succinonitrile (SN), ethylene sulfate (ESa), 1,3-propene sultone (PRS), fluoroethylene carbonate (FEC), adiponitrile (ADN), LiPO2F2, lithium difluorobis(oxalate)phosphate (LiODFB), lithium bis(oxalate)borate (LiBOB), (trimethylsilyl)propyl phosphate (TMSPa), (trimethylsilyl)propyl phosphate (TMSPi), TFEPa, and TFEPi, without limitation.
[0143] Conventionally, in a general electrolyte, metal ions eluted from the positive electrode are precipitated at the negative electrode, whereas the gel polymer electrolyte of the present invention contains a matrix polymer formed by an oligomer, and thus can secure the effect of improving ion conductivity through the effects of increasing high voltage safety and reducing battery resistance as well as mechanical properties. Therefore, a lithium secondary battery having improved life characteristics and capacity characteristics can be manufactured. In addition, a protective layer made of a polymer is formed on the surface of the positive electrode and the negative electrode, or an anion is stabilized using a polymer structure, thereby suppressing side reactions and increasing the adhesion between the electrodes, thereby suppressing gas generation inside the battery at high temperatures. In addition, the gel polymer can strengthen the separator, thereby improving penetration stability, improving flame retardancy, and improving stability such as overcharging through reduced volatility.
[0144] According to another embodiment of the present invention, a composition for a gel polymer electrolyte comprising a lithium salt, an electrolyte solvent, a polymerization initiator, and the oligomer including the units A to C can be provided.
[0145] The oligomer may be included in an amount of 0.5 wt% to 20 wt%, more preferably 0.5 wt% to 10 wt%, based on the total weight of the composition for gel polymer electrolyte. If the content of the oligomer is less than 0.5 wt%, gelation is difficult and the characteristics of the gel polymer electrolyte are difficult to exhibit, whereas if the content exceeds 20 wt%, the resistance increases due to the excess oligomer, which may result in a decrease in battery performance.
[0146] In the present invention, the gel polymer electrolyte of the present invention can be produced from the gel polymer electrolyte composition by using a conventionally known polymerization method.
[0147] As the polymerization initiator used in such a reaction, any of the usual polymerization initiators well known in the art can be used.
[0148] Non-limiting examples of the polymerization initiator include organic peroxides and hydroperoxides such as benzoyl peroxide, acetyl peroxide, dilauroyl peroxide, di-tert-butyl peroxide, t-butylperoxy-2-ethyl-hexanoate, cumyl hydroperoxide, and hydrogen peroxide, and azo compounds such as 2,2'-azobis(2-cyanobutane), 2,2'-azobis(methylbutyronitrile), AIBN (2,2'-azobis(isobutyronitrile)), and AMVN (2,2'-azobisdimethylvaleronitrile).
[0149] The polymerization initiator is decomposed in the battery by heat, for example, heat of 30° C. to 100° C., or at room temperature (5° C. to 30° C.) to form radicals, and the polymerizable oligomer reacts with the acrylate compound through free radical polymerization to form a gel polymer electrolyte.
[0150] In addition, the polymerization initiator may be used in an amount of 0.01 to 5 parts by weight based on 100 parts by weight of the oligomer. If the polymerization initiator exceeds 5 parts by weight, gelation may occur too quickly during injection of the composition for gel polymer electrolyte into the battery, or unreacted initiator may remain, adversely affecting the subsequent battery performance. If the polymerization initiator is less than 0.01 part by weight, gelation may not occur smoothly.
[0151] Meanwhile, as described above, the lithium salt may include any one selected from the group consisting of LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiN(C2F5SO2)2, LiN(CF3SO2)2, CF3SO3Li, LiC(CF3SO2)3, LiC4BO8, LiTFSI, LiFSI, and LiClO4, or a mixture of two or more of these, but is not limited thereto.
[0152] In addition, the electrolyte solvent may be a non-aqueous solvent commonly used in electrolytes for lithium secondary batteries, as described above, and may include, for example, at least one compound selected from the group consisting of cyclic carbonate compounds, linear carbonate compounds, alkyl ether compounds, alkyl acetate compounds, alkyl propionate compounds, and nitrile compounds.
[0153] Among them, typically, carbonate compounds which are cyclic carbonates, linear carbonates or mixtures thereof may be included.
[0154] In addition, the gel polymer electrolyte composition according to an embodiment of the present invention may selectively include other additives capable of realizing the above-mentioned physical properties known in the art, in addition to the above-mentioned components, in order to further impart performance such as an effect of increasing efficiency of gel reaction and reducing resistance.
[0155] As described above, the additive may be any of the common additives such as VC, VEC, PS, SN, AdN, ESa, PRS, FEC, LiPO2F2, LiODFB, LiBOB, TMSPa, TMSPi, TFEPa, and TFEPi, without any restrictions.
[0156] Furthermore, still another embodiment of the present invention is A positive electrode and a negative electrode, a polymer electrolyte disposed between the positive electrode and the negative electrode; The present invention provides a lithium secondary battery including a gel polymer electrolyte according to an embodiment of the present invention as the polymer electrolyte.
[0157] The gel polymer electrolyte is formed by polymerizing a composition for a gel polymer electrolyte by a conventional method known in the art. For example, the gel polymer electrolyte may be formed by in-situ polymerization of the composition for a gel polymer electrolyte inside a secondary battery.
[0158] According to a more preferred embodiment, the method may include the steps of: (a) inserting an electrode assembly including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode into a battery case; and (b) injecting a composition for a gel polymer electrolyte according to an embodiment of the present invention into the battery case and polymerizing the composition to form a gel polymer electrolyte.
[0159] The in-situ polymerization reaction in the lithium secondary battery can be carried out through E-BEAM, gamma ray, room temperature / high temperature aging process, and according to one embodiment of the present invention, through thermal polymerization. At this time, the polymerization time can be about 2 minutes to 12 hours, and the thermal polymerization temperature can be 30°C to 100°C.
[0160] More specifically, the in-situ polymerization reaction in the lithium secondary battery is carried out by adding a polymerization initiator and the oligomer in a predetermined amount to an electrolyte solution containing a lithium salt, mixing them, and then injecting the mixture into a battery cell. After sealing the inlet of the battery cell, the mixture is heated at 40°C to 80°C for 1 to 20 hours to polymerize the electrolyte solution containing the lithium salt, and a gel polymer electrolyte containing the electrolyte solution in a gel form is produced.
[0161] The lithium secondary battery according to one embodiment of the present invention has a charging voltage in the range of 3.0V to 5.0V, and has excellent capacity characteristics in both normal voltage and high voltage ranges.
[0162] Meanwhile, according to an embodiment of the present invention, the electrode constituting the lithium secondary battery may be manufactured by a conventional method well known in the art. For example, an electrode active material may be mixed and stirred with a solvent, and if necessary, a binder, a conductive material, and a dispersant to prepare a slurry, and the slurry may be applied (coated) onto a metal collector, compressed, and then dried to manufacture an electrode.
[0163] The positive electrode may be manufactured by forming a positive electrode mixture layer on a positive electrode current collector. The positive electrode mixture layer may be formed by coating a positive electrode slurry including a positive electrode active material, a binder, a conductive material, and a solvent on the positive electrode current collector, followed by drying and rolling.
[0164] The positive electrode current collector is not particularly limited as long as it has conductivity without inducing chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, fired carbon, or those obtained by surface treatment of aluminum or stainless steel with carbon, nickel, titanium, silver, etc. can be used.
[0165] The positive electrode active material is a compound capable of reversible intercalation and deintercalation of lithium. Specifically, it may include a lithium composite metal oxide containing one or more metals such as cobalt, manganese, nickel, or aluminum and lithium. More specifically, the lithium composite metal oxide includes lithium-manganese-based oxides (e.g., LiMnO2, LiMn2O4, etc.), lithium-cobalt-based oxides (e.g., LiCoO2, etc.), lithium-nickel-based oxides (e.g., LiNiO2, etc.), lithium-nickel-manganese-based oxides (e.g., LiNi 1-Y9 Mn Y9 O2 (0 < Y9 < 1), LiMn 2-z4 Ni z 4O4 (0 < Z4 < 2), etc.), lithium-nickel-cobalt-based oxides (e.g., LiNi 1-Y10 Co Y10 O2 (0 < Y10 < 1), etc.), lithium-manganese-cobalt-based oxides (e.g., LiCo 1-Y11 Mn Y11 O2 (0 < Y11 < 1), LiMn 2-z5 Co z5 O4 (0 < Z5 < 2), etc.), lithium-nickel-manganese-cobalt-based oxides (e.g., Li(Ni a Co b Mn c )O2 (0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1) or Li(Ni a1 Co b1 Mn c1 )O4 (0 < a1 < 2, 0 < b1 < 2, 0 < c1 < 2, a1 + b1 + c1 = 2), etc.), or lithium-nickel-cobalt-transition metal (M) oxides (e.g., Li(Ni a2 Co b2 Mn c2 M d)O2 (where M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, and a2, b2, c2, and d are atomic fractions of independent elements, 0 < a2 < 1, 0 < b2 < 1, 0 < c2 < 1, 0 < d < 1, and a2 + b2 + c2 + d = 1), etc.) etc. may be mentioned, and any one or two or more of these compounds may be included.
[0166] Among them, in terms of enhancing the capacity characteristics and stability of the battery, the lithium composite metal oxide is LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxide (for example, Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc.), or nickel manganese cobalt aluminum compound (for example, Li(Ni 0.86 Mn 0.045 CoAl 0.045 Al 0.05 )O2, or lithium nickel cobalt aluminum oxide (for example, Li(Ni 0.8 Co 0.15 Al 0.05 )O2, etc.) may be.
[0167] The positive electrode active material may be contained at 80% by weight to 99% by weight based on the total weight of the solid content in the positive electrode slurry.
[0168] The binder is a component that assists in binding between the active material and the conductive material, etc., and to the current collector, and is usually added in an amount of 1% by weight to 30% by weight based on the total weight of the solid content in the positive electrode slurry. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, various copolymers, etc.
[0169] The conductive material is usually added in an amount of 1% by weight to 30% by weight based on the total weight of the solid content in the positive electrode slurry.
[0170] Such a conductive material is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and examples thereof include graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives. Specific examples of commercially available conductive materials include acetylene black (manufactured by Chevron Chemical), Denka Black (manufactured by Denka Singapore Private Limited, Gulf Oil Co., Ltd., etc.), Ketjen Black EC (manufactured by Almac Co., Ltd.), Vulcan XC-72 (manufactured by Cabot Corporation), and Super P (manufactured by Timcal Corporation).
[0171] The solvent may include an organic solvent such as NMP (N-methyl-2-pyrrolidone), and may be used in an amount that provides a suitable viscosity when the positive electrode active material, and optionally a binder and a conductive material, etc. are contained. For example, the solvent may be contained so that the concentration of solids in the slurry containing the positive electrode active material, and optionally a binder and a conductive material, is 40% by weight to 60% by weight, and preferably 40% by weight to 50% by weight.
[0172] The negative electrode may be manufactured by forming a negative electrode mixture layer on a negative electrode current collector. The negative electrode mixture layer may be formed by coating a negative electrode current collector with a negative electrode slurry including a negative electrode active material, a binder, a conductive material, and a solvent, followed by drying and rolling.
[0173] The negative electrode current collector generally has a thickness of 3 μm to 500 μm. Such a negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. may be used. In addition, like the positive electrode current collector, fine irregularities may be formed on the surface to strengthen the binding force of the negative electrode active material, and it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0174] The negative electrode active material may be a lithium-containing titanium composite oxide (LTO); a carbon-based material such as non-graphitizable carbon or graphitic carbon; Li x10 Fe2O3(0≦x10≦1), Li x11 WO2(0≦x11≦1), Sn x12 Me 1-x12 Me' y12 O zMetal composite oxides such as (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x12 ≤ 1; 1 ≤ y12 ≤ 3; 1 ≤ z12 ≤ 8); lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5; and it may contain a single substance or a mixture of two or more selected from the group consisting of conductive polymers such as polyacetylene.
[0175] The negative electrode active material may be contained at 80% to 99% by weight based on the total weight of the solid content in the negative electrode slurry.
[0176] The binder is a component that assists in binding the conductive material and the active material and binding to the current collector, and is usually added at 1% to 30% by weight based on the total weight of the solid content in the negative electrode slurry. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber, fluororubber, various copolymers thereof, and the like.
[0177] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 1% by weight to 20% by weight based on the total weight of the solid content in the negative electrode slurry. Such a conductive material is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and examples of such conductive materials include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0178] The solvent may include water or an organic solvent such as NMP or alcohol, and may be used in an amount that provides a suitable viscosity when the negative electrode active material and, optionally, a binder and a conductive material are contained. For example, the solvent may be contained so that the solid content concentration in the slurry containing the negative electrode active material and, optionally, a binder and a conductive material is 50 wt % to 75 wt %, preferably 50 wt % to 65 wt %.
[0179] Then, a separator is selectively inserted between the positive and negative electrodes. The separator serves to block internal short circuits between the two electrodes and to impregnate the electrolyte. The separator may be prepared by mixing a polymer resin, a filler, and a solvent to prepare a separator composition, and then directly coating and drying the separator composition on the upper surface of an electrode to form a separator film. Alternatively, the separator composition may be cast on a support, dried, and then peeled off from the support and laminated on the upper surface of an electrode to prepare the separator film.
[0180] The polymer resin is not particularly limited, and examples thereof include chemically resistant and hydrophobic olefin-based polymers such as polypropylene; composite porous separators in which an inorganic material is added to a porous separator substrate; and sheets or nonwoven fabrics made of glass fibers or polyethylene.
[0181] The pore size of the porous separation membrane may generally be 0.01 μm to 50 μm, the porosity may be 5% to 95%, and the thickness of the porous separation membrane may generally be 5 μm to 300 μm.
[0182] The external shape of the lithium secondary battery according to an embodiment of the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.
[0183] [Example] Example 1 (Positive electrode active material: NCMA) (1) Preparation of composition for gel polymer electrolyte Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 3:7, and LiPF6 and LiFSI were added at 0.5M and 0.5M, respectively, to prepare a mixed solvent. The oligomer represented by the formula 5 (weight average molecular weight 6,000, p:q=2:1, r=3) was added to the mixed solvent in an amount of 5wt% based on 100wt% of the composition for gel polymer electrolyte. In addition, 0.1wt% of a polymerization initiator (AIBN), 1.5wt% of vinylene carbonate (VC), and 1wt% of propane sultone (PS) were added thereto to prepare a composition for gel polymer electrolyte. Table 1 below shows the components and contents of the composition for gel polymer electrolyte of Example 1.
[0184] [Table 1]
[0185] (2) Manufacture of lithium secondary batteries As a positive electrode active material (LiNi 0.86 Co 0.045 Mn 0.045 Al 0.05A positive electrode mixture slurry was prepared by adding 94% by weight of O2, 3% by weight of carbon black as a conductive material, and 3% by weight of PVDF as a binder to a solvent, N-methyl-2-pyrrolidone (NMP). The positive electrode mixture slurry was applied to an aluminum (Al) thin film as a positive electrode current collector having a thickness of about 20 μm, dried, and then roll-pressed to prepare a positive electrode.
[0186] Anode active material carbon powder, binder PVDF, and conductive material carbon black were added to a solvent NMP at 96 wt%, 3 wt%, and 1 wt%, respectively, to prepare anode mixture slurry. The anode mixture slurry was applied to a 10 μm-thick copper (Cu) thin film as anode current collector, dried, and then roll-pressed to prepare anode.
[0187] An electrode assembly was prepared using the positive electrode, the negative electrode, and a separator consisting of three layers of polypropylene / polyethylene / polypropylene (PP / PE / PP), and the gel polymer electrolyte composition prepared as described above was poured into the electrode assembly, and the electrode assembly was left for two days and then heated at 60° C. for 24 hours to prepare a lithium secondary battery containing a gel polymer electrolyte. The nominal voltage of the obtained battery was 2.5V to 4.2V.
[0188] Example 2 (Positive electrode active material: LCO) (1) Preparation of composition for gel polymer electrolyte A gel polymer electrolyte composition was produced in the same manner as in Example 1, except that the composition was as shown in Table 2 below.
[0189] [Table 2]
[0190] (2) Manufacture of lithium secondary batteries A positive electrode mixture slurry was prepared by adding 94 wt% of LiCoO2 (LCO) as a positive electrode active material, 3 wt% of carbon black as a conductive material, and 3 wt% of PVDF as a binder to a solvent, N-methyl-2-pyrrolidone (NMP). The positive electrode mixture slurry was applied to an aluminum (Al) thin film as a positive electrode current collector having a thickness of about 20 μm, dried, and then roll-pressed to prepare a positive electrode.
[0191] Anode active material carbon powder, binder PVDF, and conductive material carbon black were added to a solvent NMP at 96 wt%, 3 wt%, and 1 wt%, respectively, to prepare anode mixture slurry. The anode mixture slurry was applied to a 10 μm-thick copper (Cu) thin film as anode current collector, dried, and then roll-pressed to prepare anode.
[0192] An electrode assembly was prepared using the positive electrode, the negative electrode, and a separator consisting of three layers of polypropylene / polyethylene / polypropylene (PP / PE / PP), and the gel polymer electrolyte composition prepared as described above was poured into the electrode assembly, and the electrode assembly was left for two days and then heated at 60° C. for 24 hours to prepare a lithium secondary battery containing a gel polymer electrolyte. The nominal voltage of the battery was 3.0V to 4.45V.
[0193] Example 3 (Positive electrode active material: LFP) (1) Preparation of composition for gel polymer electrolyte Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 3:4:3, and 1M of LiPF6 was added to prepare a mixed solvent. The oligomer represented by the formula 5 (weight average molecular weight 6,000, p:q=2:1r=3) was added to the prepared mixed solvent in an amount of 3wt% based on 100wt% of the composition for gel polymer electrolyte. In addition, 0.1wt% of a polymerization initiator (AIBN) and 2.5wt% of vinylene carbonate (VC) were added thereto to prepare a composition for gel polymer electrolyte. Table 3 below shows the components and contents of the composition for gel polymer electrolyte of Example 3.
[0194] [Table 3]
[0195] (2) Manufacture of lithium secondary batteries A positive electrode mixture slurry was prepared by adding 94 wt% of LiFePO4 (LFP) as a positive electrode active material, 3 wt% of carbon black as a conductive material, and 3 wt% of PVDF as a binder to a solvent, N-methyl-2-pyrrolidone (NMP). The positive electrode mixture slurry was applied to an aluminum (Al) thin film as a positive electrode current collector having a thickness of about 20 μm, dried, and then roll-pressed to prepare a positive electrode.
[0196] Anode active material carbon powder, binder PVDF, and conductive material carbon black were added to a solvent NMP at 96 wt%, 3 wt%, and 1 wt%, respectively, to prepare anode mixture slurry. The anode mixture slurry was applied to a 10 μm-thick copper (Cu) thin film as anode current collector, dried, and then roll-pressed to prepare anode.
[0197] An electrode assembly was prepared using the positive electrode, the negative electrode, and a separator consisting of three layers of polypropylene / polyethylene / polypropylene (PP / PE / PP), and the gel polymer electrolyte composition prepared as described above was poured into the electrode assembly, and the electrode assembly was left for two days and then heated at 60° C. for 24 hours to prepare a lithium secondary battery containing a gel polymer electrolyte. The nominal voltage of the battery was 2.5 V to 3.6 V, and the capacity was 720 mAh.
[0198] Comparative Example 1 (using liquid electrolyte, NCMA) (1) Electrolyte production Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 3:7, and LiPF6 was added at 1.0 M to prepare an electrolyte solution by mixing 97 g of the mixed solvent with 1.5 g of VC and 1.5 g of PS as other additives. Table 4 below shows the components and contents of the electrolyte composition of Comparative Example 1.
[0199] [Table 4]
[0200] (2) Manufacture of lithium secondary batteries As a positive electrode active material (LiNi 0.86 Co 0.045 Mn 0.045 Al 0.05 A positive electrode mixture slurry was prepared by adding 94% by weight of O2, 3% by weight of carbon black as a conductive material, and 3% by weight of PVDF as a binder to a solvent, N-methyl-2-pyrrolidone (NMP). The positive electrode mixture slurry was applied to an aluminum (Al) thin film as a positive electrode current collector having a thickness of about 20 μm, dried, and then roll-pressed to prepare a positive electrode.
[0201] Anode active material carbon powder, binder PVDF, and conductive material carbon black were added to a solvent NMP at 96 wt%, 3 wt%, and 1 wt%, respectively, to prepare anode mixture slurry. The anode mixture slurry was applied to a 10 μm-thick copper (Cu) thin film as anode current collector, dried, and then roll-pressed to prepare anode.
[0202] An electrode assembly was prepared using the positive electrode, the negative electrode, and a separator having three layers of polypropylene / polyethylene / polypropylene (PP / PE / PP), and the electrolyte prepared as described above was injected into the electrode assembly to prepare a lithium secondary battery.
[0203] Comparative Example 2 (Liquid Electrolyte Used, LCO) A lithium secondary battery was manufactured in the same manner as in Comparative Example 1, except that (LiCoO2; LCO) was used as the positive electrode active material.
[0204] Comparative Example 3 (Liquid electrolyte used, LFP) (1) Electrolyte production An electrolyte solution was prepared according to the composition in Table 5 below.
[0205] [Table 5]
[0206] (2) Manufacture of lithium secondary batteries A positive electrode mixture slurry was prepared by adding 94 wt% of LiFePO4 (LFP) as a positive electrode active material, 3 wt% of carbon black as a conductive material, and 3 wt% of PVDF as a binder to a solvent, N-methyl-2-pyrrolidone (NMP). The positive electrode mixture slurry was applied to an aluminum (Al) thin film as a positive electrode current collector having a thickness of about 20 μm, dried, and then roll-pressed to prepare a positive electrode.
[0207] Anode active material carbon powder, binder PVDF, and conductive material carbon black were added to a solvent NMP at 96 wt%, 3 wt%, and 1 wt%, respectively, to prepare anode mixture slurry. The anode mixture slurry was applied to a 10 μm-thick copper (Cu) thin film as anode current collector, dried, and then roll-pressed to prepare anode.
[0208] An electrode assembly was prepared using the positive electrode, the negative electrode, and a separator consisting of three layers of polypropylene / polyethylene / polypropylene (PP / PE / PP), and the electrolyte prepared as described above was injected into the electrode assembly to prepare a lithium secondary battery. The nominal voltage of the battery was 2.5V to 3.6V, and the capacity was 720mAh.
[0209] Comparative Example 4 (using gel polymer electrolyte, LFP) (1) Preparation of composition for gel polymer electrolyte Ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 3:4:3, and LiPF6 was added at 1M to prepare a mixed solvent, and then an oligomer (weight average molecular weight 6,000, m2:n2=2:1, o2=6) represented by the following chemical formula z was added to the prepared mixed solvent in an amount of 3wt% relative to 100wt% of the composition for gel polymer electrolyte. In addition, 0.1wt% of a polymerization initiator (AIBN) and 2.5wt% of vinylene carbonate (VC) were added thereto to prepare a composition for gel polymer electrolyte.
[0210] [ka]
[0211] Here, m2, n2, and o2 are the numbers of repeating units, m2 is any one integer from 1 to 10, n2 is any one integer from 1 to 10, and o2 is any one integer from 1 to 500.
[0212] [Table 6]
[0213] (2) Manufacture of lithium secondary batteries A positive electrode mixture slurry was prepared by adding 94 wt% of LiFePO4 (LFP) as a positive electrode active material, 3 wt% of carbon black as a conductive material, and 3 wt% of PVDF as a binder to a solvent, N-methyl-2-pyrrolidone (NMP). The positive electrode mixture slurry was applied to an aluminum (Al) thin film as a positive electrode current collector having a thickness of about 20 μm, dried, and then roll-pressed to prepare a positive electrode.
[0214] Anode active material carbon powder, binder PVDF, and conductive material carbon black were added to a solvent NMP at 96 wt%, 3 wt%, and 1 wt%, respectively, to prepare anode mixture slurry. The anode mixture slurry was applied to a 10 μm-thick copper (Cu) thin film as anode current collector, dried, and then roll-pressed to prepare anode.
[0215] An electrode assembly was prepared using the positive electrode, the negative electrode, and a separator consisting of three layers of polypropylene / polyethylene / polypropylene (PP / PE / PP), and the gel polymer electrolyte composition prepared as above was poured into the electrode assembly, and the electrode assembly was left for two days and then heated at 60° C. for 24 hours to prepare a lithium secondary battery containing a gel polymer electrolyte. The nominal voltage of the battery was 2.5 V to 3.6 V, and the capacity was 720 mAh.
[0216] [Experimental Example] Experimental Example 1: Experiment on heat generation safety (Example 1 and Comparative Example 1) After the battery was manufactured, an additional exothermic reaction was observed while the battery was heated in a fully charged state. The heat flux was measured using a multiple module calorimetry (MMC) at a heating rate of 0.2° C. / min up to 300° C. Meanwhile, referring to FIG. 1 and Table 7, the first peak was confirmed to be 137.4 J in the example and 156.9 J in the comparative example, and the second peak was confirmed to be 127.4 J in the example and 166.4 J in the comparative example.
[0217] [Table 7]
[0218] In the case of the beaker cell manufactured according to Example 1, it was confirmed that the current rapidly increased at a voltage range lower than the voltage range where a normal electrolyte is decomposed. This is believed to be due to the increase in current (A) caused by the decomposition of the overcharge prevention additive contained in the electrolyte. On the other hand, in the case of the beaker cell manufactured according to Comparative Example 1, it was confirmed that the current increased at a voltage range higher than that of the examples.
[0219] Experimental Example 2: Evaluation experiment of high temperature capacity retention rate and resistance increase rate (Example 1 and Comparative Example 1) The batteries of Example 1 and Comparative Example 1 were charged to SOC 100% and then maintained at 60° C. for 4 weeks.
[0220] The capacity retention rate was measured as follows. At the start of the experiment, the battery was charged to 4.2 V at 1 C in a thermostatic chamber at 60°C, discharged to 2.5 V, and the capacity at this time was measured. After that, while maintaining the battery in the chamber, it was charged to 4.2 V at 1 C at predetermined intervals and discharged to 2.5 V, and the capacity at each time was measured. This was continued for 4 weeks. The initially measured capacity was set to 100%, and each capacity value measured thereafter was calculated as a percentage.
[0221] Meanwhile, the resistance increase rate was measured as follows: For the batteries obtained in each Example 1 and Comparative Example 1, a pulse discharge (DC-IR measurement) was performed for each SOC section using a hybrid pulse power characterization (HPPC) method, and the resistance was recorded. The resistance was calculated by dividing the voltage change that occurred during discharge by the discharge current according to the following Equation 1. R=V / I … Formula 1 Here, R is the resistance, V is the voltage change that occurs during discharge, and I is the discharge current.
[0222] [Table 8]
[0223] The results are summarized in Table 8 and Figure 2. It can be seen from Table 8 and Figure 2 that the gel polymer electrolyte of the present invention does not affect the capacity or resistance of the battery, as compared with the case where a liquid electrolyte is used.
[0224] Experimental Example 3: Evaluation of low-temperature life characteristics (Example 2 and Comparative Example 2) The batteries of Example 2 and Comparative Example 2 were charged / discharged at an ambient temperature of 15° C. to measure the capacity. -Charging conditions: 2C, CC (constant current) / CV (constant voltage) (4.45V, 0.05C current cutoff) -Discharge conditions: 1C, CC (constant current) conditions, 3V The battery was then charged / discharged 200 times at the same current and voltage range. The capacity retention rate was calculated according to the following formula 2. Capacity retention rate (%) = [discharge capacity after 200 cycles / charge capacity after 1 cycle] x 100 … Formula 2
[0225] Experimental Example 4: Evaluation of room temperature life characteristics (Example 2 and Comparative Example 2) The batteries of Example 2 and Comparative Example 2 were charged / discharged at an ambient temperature of 25° C. to measure the capacity. -Charging conditions: 2C, CC (constant current) / CV (constant voltage) (4.45V, 0.05C current cutoff) -Discharge conditions: 1C, CC (constant current) conditions, 3V
[0226] The battery was then charged / discharged 300 times at the same current and voltage range. The capacity retention rate was calculated according to the following formula 3. Capacity retention rate (%) = [discharge capacity after 300 cycles / charge capacity after 1 cycle] x 100 … Formula 3
[0227] [Table 9]
[0228] Referring to Table 9, the battery according to Example 2 exhibited a capacity retention rate at the same level as the battery using a conventional liquid electrolyte. In particular, it was confirmed that the capacity retention rate of the battery according to Example 2 after repeated charging and discharging under low temperature conditions was superior to that of the battery according to Comparative Example 2.
[0229] Experimental Example 5: High-temperature storage characteristics (Example 2 and Comparative Example 2) The batteries of Example 2 and Comparative Example 2 were left in a chamber at 60° C. and 90% relative humidity for 7 days, and the capacity maintenance rate and capacity recovery rate were evaluated.
[0230] The capacity retention rate was measured as follows. At the start of the experiment, the battery was charged and discharged once under the charge and discharge conditions of Experimental Example 4, and the capacity at this time was measured. Next, the battery was left in a chamber at 60°C and 90% relative humidity for 7 days, and then removed from the chamber and charged to 4.45V at 0.2C, and discharged until it reached 3V, and the capacity at this time was measured. The initially measured capacity was set to 100% and the remaining capacity was calculated in %.
[0231] Then, each battery was left at room temperature for a certain period of time, and then charged and discharged from 3V to 4.45V at 0.2C and 0.1C, respectively, to measure the capacity. The capacity relative to the initially measured capacity of 100% was calculated to obtain the capacity recovery rate (%).
[0232] [Table 10]
[0233] Referring to Table 10, the battery according to Example 2 exhibited a capacity retention rate at the same level as that of the battery using a conventional liquid electrolyte. In particular, it was confirmed that the capacity retention rate of the battery according to Example 2 after repeated charging and discharging under low temperature conditions was superior to that of the battery according to Comparative Example 2.
[0234] Experimental Example 6: Hot Box Profile (Example 2 and Comparative Example 2) The batteries of Example 2 and Comparative Example 2 were subjected to a hot box test. The batteries of Example 2 and Comparative Example 2 were charged to SOC 100%, placed in a temperature-controllable chamber, heated to 140°C at a rate of 5°C / min, and maintained at that temperature for at least 1 hour. Figure 3 shows the hot box test results for the batteries of Example 2 and Figure 4 shows the hot box test results for the batteries of Comparative Example 2.
[0235] 3 and 4, it can be seen that the battery of Example 2 has a significantly longer voltage retention time than the battery of Comparative Example 2. Meanwhile, the battery of Comparative Example 2 suddenly rose in temperature after 30 minutes, exploded, and became unable to operate. This confirmed that the battery of Example 2 has superior heat resistance to the battery of Comparative Example 2.
[0236] Figure 6 is a photographic image of the battery of Example 2 that underwent hot box testing, and Figure 7 is a photographic image of the battery of Comparative Example 2 that underwent hot box testing. The battery in Figure 7 was damaged by an explosion.
[0237] Experimental Example 7: Comparison of life characteristics and thickness increase rate (Example 2 and Comparative Example 2) The batteries of Example 2 and Comparative Example 2 were charged / discharged at an ambient temperature of 25° C. to measure the capacity. Each battery was charged in CC (constant current) / CV (constant voltage) mode up to 4.45 V while changing the rate limit to 2 C, 1.5 C, and 1 C, with a cutoff current of 0.05 C. Discharge was performed under 1 C and CC (constant current) conditions up to 3 V. Charge / discharge was repeated 400 times under the same conditions.
[0238] FIG. 5 shows the capacity of the batteries of Example 2 and Comparative Example 2. As shown in FIG. 5, it was confirmed that the batteries of Example 2 and Comparative Example 2 have similar capacity change rates. In addition, both the battery of Example 2 and the battery of Comparative Example 2 showed a capacity retention rate of 78% at the 400th cycle. In addition, it was confirmed that the batteries of Example 2 and Comparative Example 2 had an increase in thickness of less than 5.76 mm after 400 cycles. This confirms that the battery of Example 2 has electrochemical properties at a similar level to batteries using conventional liquid electrolytes.
[0239] Experimental Example 8 (Example 3, Comparative Example 3 and Comparative Example 4) The batteries of Example 3, Comparative Example 3, and Comparative Example 4 were charged / discharged three times at 2.5V to 3.6V, and then maintained in a thermostatic chamber at 60°C for six weeks at SOC 100%. Then, the room temperature resistance at SOC 50% was measured to confirm the difference in the increase rate for the same resistance of the initial battery.
[0240] [Table 11]
[0241] It has been confirmed that the battery according to the present invention further improves the resistance increase rate by effectively suppressing the reaction between the electrode and the additive / electrolyte.
Claims
1. A matrix polymer and an electrolyte impregnated in the matrix polymer, The matrix polymer is formed into a three-dimensional network structure by polymerization of an oligomer represented by the following Chemical Formula 1: The electrolyte solution includes a lithium salt and a non-aqueous solvent, The non-aqueous solvent includes at least one selected from the group consisting of a cyclic carbonate-based compound, a linear carbonate-based compound, an alkyl ether-based compound, an alkyl acetate-based compound, an alkyl propionate-based compound, and a nitrile-based compound; 【Chemistry 1】 In Chemical Formula 1, r is an integer of 1 or more, R 1 each represents an aliphatic hydrocarbon group or an aromatic hydrocarbon group, R 2 and R 5 each independently represents an alkyl group having 1 to 3 carbon atoms in which at least one hydrogen atom has been substituted with a fluorine atom, R 3 is an alkyl group having n carbon atoms in which all hydrogen atoms are substituted with fluorine; R 4 is an alkyl group having n-1 carbon atoms in which all hydrogen atoms have been substituted with fluorine, where n is 2 or 3; Either one of p and q is 0 or both are integers of 1 or more, and when both p and q are integers of 1 or more, p / q has a value of 1 / 9 to 9 / 1; R 6 and R 7 are each independently a linear or branched alkyl group having 1 to 5 carbon atoms, The R 8 is null or a methyl group, and m is an integer of 1, 2, 3, 4, or 5; Gel polymer electrolyte.
2. The oligomer includes a unit A represented by the following formula 2, a unit B represented by the following formula 3, and a unit C represented by the following formula 4: 【Chemistry 2】 【Chemistry 3】 【Chemistry 4】 In Chemical Formula 2, Chemical Formula 3, and Chemical Formula 4, r is an integer of 1 or more, R 1 each represents an aliphatic hydrocarbon group or an aromatic hydrocarbon group, R 2 and R 5 each independently represents an alkyl group having 1 to 3 carbon atoms in which at least one hydrogen atom has been substituted with a fluorine atom, R 3 is an alkyl group having n carbon atoms in which all hydrogen atoms are substituted with fluorine; R 4 is an alkyl group having n-1 carbon atoms in which all hydrogen atoms have been substituted with fluorine, where n is 2 or 3; Either one of p and q is 0 or both are integers of 1 or more, and when both p and q are integers of 1 or more, p / q has a value of 1 / 9 to 9 / 1; R 6 and R 7 are each independently a linear or branched alkyl group having 1 to 5 carbon atoms, The R 8 The gel polymer electrolyte according to claim 1 , wherein m is null or a methyl group, and m is any one of the integers 1, 2, 3, 4, and 5.
3. The formula 2 is divided into a unit represented by the following formula 2-1 and a unit represented by the following formula 2-2: 【Chemistry 5】 【Chemistry 6】 In Chemical Formula 2-2, R 1 The gel polymer electrolyte according to claim 2 , wherein is an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, or an aromatic hydrocarbon group.
4. the aliphatic hydrocarbon group is an alkylene group having 1 to 20 carbon atoms; an alkylene group having 1 to 20 carbon atoms and containing an isocyanate group (NCO); an alkoxylene group having 1 to 20 carbon atoms; an alkenylene group having 2 to 20 carbon atoms; or an alkynylene group having 2 to 20 carbon atoms; the alicyclic hydrocarbon group is a substituted or unsubstituted cycloalkylene group having 4 to 20 carbon atoms; a substituted or unsubstituted cycloalkylene group containing an isocyanate group (NCO) and having 4 to 20 carbon atoms; a cycloalkenylene group having 4 to 20 carbon atoms; or a heterocycloalkylene group having 2 to 20 carbon atoms; 4. The gel polymer electrolyte according to claim 3, wherein the aromatic hydrocarbon group is a substituted or unsubstituted arylene group having 6 to 20 carbon atoms; or a heteroarylene group having 2 to 20 carbon atoms.
5. The gel polymer electrolyte according to claim 4, wherein the compound represented by the formula 2-2 is derived from any one of the compounds represented by the following formulas a to n: 【Chemistry 7】 【Chemistry 8】 【Chemistry 9】 【Chemistry 10】 【Chemistry 11】 【Chemistry 12】 【Chemistry 13】 【Chemistry 14】 【Chemistry 15】 【Chemistry 16】 【Chemistry 17】 【Chemistry 18】 【Chemistry 19】 【Chemistry 20】
6. The gel polymer electrolyte according to claim 4, wherein the structure represented by the chemical formula 2-2 is any one or more of the structures represented by the following chemical formulas o to x. 【Chemistry 21】 【Chemical 22】 【Chemistry 23】 【Chemistry 24】 【Chemistry 25】 【Chemistry 26】 【Chemical 27】 【Chemistry 28】 【Chemical Formula 29】 【Chemistry 30】
7. The gel polymer electrolyte according to claim 2 , wherein the oligomer of Chemical Formula 4 has (meth)acryloyl groups at both ends of the oligomer of Chemical Formula 1.
8. The gel polymer electrolyte of claim 1 , wherein the oligomer comprises a compound represented by the following formula 5: 【Chemistry 31】
9. 2. The gel polymer electrolyte of claim 1, wherein the weight average molecular weight (Mw) of the oligomer is from about 1,000 g / mol to 500,000 g / mol.
10. The gel polymer electrolyte according to claim 1 , wherein the matrix polymer further comprises 5 to 700 parts by weight of inorganic particles based on 100 parts by weight of the oligomer.
11. The gel polymer electrolyte according to claim 1 , wherein the gel polymer electrolyte has a gel content of about 1% by weight or more at a temperature of 25° C.
12. A negative electrode, a positive electrode, and a gel polymer electrolyte, A lithium ion secondary battery, wherein the gel polymer electrolyte is the gel polymer electrolyte according to claim 1 .
13. The present invention includes a lithium salt, a non-aqueous solvent, a polymerization initiator, and an oligomer represented by the following Chemical Formula 1: The oligomer is included in an amount of 0.5% by weight to 20% by weight based on the total weight of the composition for the gel polymer electrolyte, 【Chemistry 32】 In Chemical Formula 1, r is an integer of 1 or more, R 1 each represents an aliphatic hydrocarbon group or an aromatic hydrocarbon group, R 2 and R 5 each independently represents an alkyl group having 1 to 3 carbon atoms in which at least one hydrogen atom has been substituted with a fluorine atom, R 3 is an alkyl group having n carbon atoms in which all hydrogen atoms are substituted with fluorine; R 4 is an alkyl group having n-1 carbon atoms in which all hydrogen atoms have been substituted with fluorine, where n is 2 or 3; Either one of p and q may be 0 or both may be integers of 1 or more. When both p and q are integers of 1 or more, p / q has a value of 1 / 9 to 9 / 1; R 6 and R 7 are each independently a linear or branched alkyl group having 1 to 5 carbon atoms, The R 8 is null or a methyl group, and m is any one of integers 1, 2, 3, 4, and 5.
Citation Information
Patent Citations
Nonaqueous electrolyte and lithium secondary battery containing the same
JP2021513188A
Gel polymer electrolyte and lithium secondary battery including the same
US20180342767A1
Lithium Secondary Battery Having Improved High-Temperature Characteristics
US20210036365A1